Terrorism before the letter: mythography and political violence in England, Scotland, and France 1559-1642 - Appelbaum, Robert (Oxford University Press, 2015)
Beginning around 1559 and continuing through 1642, writers in England, Scotland, and France found themselves pre-occupied with an unusual sort of crime, a crime without a name which today we call 'terrorism'. These crimes were especially dangerous because they were aimed at violating not just the law but the fabric of law itself; and yet they were also, from an opposite point of view, especially hopeful, for they seemed to have the power of unmaking a systematic injustice and restoring a nation to its 'ancient liberty'. The Bible and the annals of classical history were full of examples: Ehud assassinating King Eglon of Moab; Samson bringing down the temple in Gaza; Catiline arousing a conspiracy of terror in republican Rome; Marcus Brutus leading a conspiracy against the life of Julius Caesar. More recent history provided examples too: legends about Mehmed II and his concubine Irene; the assassination in Florence of Duke Alessandro de 'Medici, by his cousin Lorenzino.0